RETRACTED: Recommendations for bureaucracy services in the new normal time - Rifky Azis; Nurul Husna (Monas: Jurnal Inovasi Aparatur, 2022)
This article has been retracted. This article has been retracted at the author's request and the Editor-in-Chief's approval. The author has multiple submissions and publications to another journal: AZIS, Rifky Febrihanuddin; HUSNA, Nurul; HANUM, Roro. Rekomendasi Pelayanan Birokrasi di Masa Transisi Pandemi Covid-19. Tapis : Jurnal Penelitian Ilmiah, [S.l.], v. 6, n. 2, p. 179-188, dec. 2022. ISSN 2580-068X. Available at: <https://e-journal.metrouniv.ac.id/index.php/tapis/article/view/6652> doi: https://doi.org/10.32332/tapis.v6i2.6652.